Hyperthermic-related challenges in aquatics, athletics, football, tennis and triathlon - Mountjoy, M.; Alonso, J.-M.; Bergeron, M. F.; Dvorak, J.; Miller, S.; Migliorini, S.; Singh, D. G. (British Journal of Sports Medicine, 2012)
Although many elite sporting events occur in climate-controlled venues, some athletes train and compete in environments that can potentially pose a risk to the athlete's health. In particular, athletes in aquatics, track and field, tennis, football and triathlon can be exposed to extreme heat during competition or while training. The International Federations responsible for these sports are aware of these health risks and have implemented measures to help protect the health of their athletes. This review paper outlines the sport-specific environmental health risks and the safety standards implemented to safeguard athlete health.